2004
DOI: 10.1056/nejmoa032706
|View full text |Cite
|
Sign up to set email alerts
|

A Trial of Three Antiretroviral Regimens in HIV-1–Infected Children

Abstract: In this phase 1-2 trial involving HIV-1-infected children, an age of three months or younger at the initiation of therapy and treatment with stavudine, lamivudine, nevirapine, and nelfinavir were associated with improved long-term viral suppression. Larger, randomized trials are required to define the optimal time to initiate therapy and the optimal regimen for these infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
88
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(95 citation statements)
references
References 11 publications
5
88
1
1
Order By: Relevance
“…All infants received postnatal antiretroviral therapy with either stavudine, abacavir, nevirapine, or nelfinavir in combination with lamivudine and zidovudine. The results of these PACTG studies have been presented separately elsewhere (1,6,12,15). The human-subject committee at each participating clinical site approved these studies.…”
Section: Methodsmentioning
confidence: 99%
“…All infants received postnatal antiretroviral therapy with either stavudine, abacavir, nevirapine, or nelfinavir in combination with lamivudine and zidovudine. The results of these PACTG studies have been presented separately elsewhere (1,6,12,15). The human-subject committee at each participating clinical site approved these studies.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, to evaluate positive responses to pneumococcal polysaccharide vaccine (PPV) the use of arbitrary levels is less accurate than comparing fold increase from baseline (39) and the presence of opsonizing antibodies should be considered. Finally, post vaccination pneumococcal IgG levels seem to be reduced in treatment naïve and HAART-treated HIV-1-infected patients (40,41). The mechanisms underlying this condition are poorly known.…”
Section: Figmentioning
confidence: 99%
“…Several small prospective and retrospective studies in developed countries have suggested that ART initiated early in life could prevent this rapid clinical and immunologic deterioration [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%